2015
DOI: 10.1210/jc.2014-4167
|View full text |Cite
|
Sign up to set email alerts
|

Primary Aldosteronism andARMC5Variants

Abstract: Germline ARMC5 variants may be associated with primary aldosteronism. Additional cohorts of patients with primary aldosteronism and metabolic syndrome, particularly African Americans, should be screened for ARMC5 sequence variants because these may underlie part of the known increased predisposition of African Americans to low renin hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(73 citation statements)
references
References 55 publications
(59 reference statements)
3
69
0
1
Order By: Relevance
“…To determine if such germ-line variants may predispose to APCC accumulation, APCC score, or mutation status of genes somatically altered in APA, we performed Sanger sequencing of the ARMC5 coding sequence on germ-line DNA isolated from five adrenals with the highest APCC scores (DAN8, -11, -15, -21, and -26). Only one adrenal (DAN15) had a nonsynonymous alteration (P507L), which was previously reported as benign based on in silico analysis (34). Hence, although our results do not support a role for germ-line variants in ARMC5 driving APCC accumulation, determining genetic associations with APCC development is an important area for future research.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…To determine if such germ-line variants may predispose to APCC accumulation, APCC score, or mutation status of genes somatically altered in APA, we performed Sanger sequencing of the ARMC5 coding sequence on germ-line DNA isolated from five adrenals with the highest APCC scores (DAN8, -11, -15, -21, and -26). Only one adrenal (DAN15) had a nonsynonymous alteration (P507L), which was previously reported as benign based on in silico analysis (34). Hence, although our results do not support a role for germ-line variants in ARMC5 driving APCC accumulation, determining genetic associations with APCC development is an important area for future research.…”
Section: Discussionmentioning
confidence: 51%
“…Recently, PA was found to associate with germ-line mutations in armadillo repeat containing 5 (ARMC5) (34). To determine if such germ-line variants may predispose to APCC accumulation, APCC score, or mutation status of genes somatically altered in APA, we performed Sanger sequencing of the ARMC5 coding sequence on germ-line DNA isolated from five adrenals with the highest APCC scores (DAN8, -11, -15, -21, and -26).…”
Section: Discussionmentioning
confidence: 99%
“…The investigation of a cohort of 56 patients with primary hyperaldosteronism showed 10.7% of ARMC5 variants predicted pathogenic by in silico analysis in African-American patients. Two of these patients had bilateral adrenal hyperplasia and co-secretion of aldosterone and cortisol (41). Whether this applies to other populations remains to be demonstrated.…”
Section: Armc5 Mutations and Phenotype In Pbmah "mentioning
confidence: 94%
“…Another interesting observation is that ARMC5-mutated patients have hypertension more often than WT patients. A more severe hypercortisolism is probably one of the major explanations, but it has been recently suggested that ARMC5 mutation could favor hypertension with low renin hyperaldosteronism in the African-American population (41). The investigation of a cohort of 56 patients with primary hyperaldosteronism showed 10.7% of ARMC5 variants predicted pathogenic by in silico analysis in African-American patients.…”
Section: Armc5 Mutations and Phenotype In Pbmah "mentioning
confidence: 99%
See 1 more Smart Citation